Development of French Learning Materials Using the Thinglink Site at SMAN 2 Tarutung - Desi Rohani Siagian; Junita Friska (International Journal of Educational and Life Sciences, 2023)
This study aims to develop teaching materials on French learning material "Les endroits publics" using the Thinglink site for class X MIA 3 at SMA Negeri 2 Tarutung. This research uses the Research and Development (R&D) method of the ADDIE development model by Dick and Carry which consists of analysis, design, development, implementation and evaluation. This research is limited to 3 stages, namely analysis, design and development. The first stage is the analysis of student needs by analyzing materials, interviews, questionnaires and student task analysis. The second stage is design, which is designing materials and media into products that are suitable for use in the learning process. The third stage is the development of teaching materials on les endroits publics using the thinglink site. The teaching materials developed will be validated by material experts and media experts. The material validation test results with a score of 87 while the media validation results are 96. The results of material validation are categorized as very good and media validation is categorized as very good. Thus it can be concluded that the development of French learning materials using the Thinglink site is declared feasible to use for French learning at SMA Negeri 2 Tarutung